The Relationship of Plasma Aterogenity Index and Mean Platelet Volume with the Risk of Development of 1-Year Total Major Adverse Cardiac Event in Patients with Non-ST Elevation Myocardial Infarction - Allahverdiyev, Agil; Koyuncu, Irem Muge Akbulut; Kuru, Busra; Allahverdiyeva, Aytac; Ertas, Fatih Sinan (International Journal of Angiology, 2023)
In our study, we aimed to reveal the role of plasma atherogenicity index and mean platelet volume in predicting the risk of developing a 1-year major adverse cardiac event (MACE) in patients with non-ST elevation myocardial infarction (NSTEMI).This study, which was planned from the retrospective cross-sectional study model, was performed with 100 patients diagnosed with NSTEMI and scheduled for coronary angiography. The laboratory values of the patients were evaluated, the atherogenicity index of plasma was calculated, and the 1-year MACE status was evaluated.In total, 79 of the patients were male and 21 were female. The average age is 60.8 years. At the end of the first year, the MACE improvement rate was found to be 29%. The PAI value was below 0.11 in 39% of the patients, between 0.11 and 0.21 in 14%, and above 0.21 in 47%. The 1-year MACE development rate was found to be significantly higher in diabetic patients and patients with hyperlipidemia. Lymphocyte count and triglyceride values of the patients in the high-risk group of atherogenic index of plasma (AIP) were found to be higher than the patients in the low-risk group. The neutrophil/lymphocyte, thrombocyte/lymphocyte ratios and high-density lipoprotein values of the patients in the high-risk group of AIP were found to be lower than those in the low-risk group. The rate of MACE development was found to be significantly higher in patients in the high-risk group of AIP (p = 0.02). No correlation was found between the mean platelet volume and the MACE development status.While no significant relationship was found between MPV and MACE in NSTEMI patients, AIP, which includes atherogenic parameters, was found to be correlated with MACE.
Keywords: NSTEMI; atherogenic index of plasma; mean platelet volume